AD-Frames satisfying Property B - Kaushik, S. K.; Kumar, Varinder (Communications in Mathematics and Applications, 2012)
AD-frames in Banach spaces have been introduced and studied. Some necessary conditions for existence of AD-frames have been given. Property B for AD-frames is defined and a characterization of AD-frames satisfying property B has been obtained. Also, we gave a sufficient condition for an AD-frame to satisfy property B and a necessary condition for a particular type of AD-frame satisfying property B. Finally, a result regarding quasi-reflexivity of Banach spaces having AD-frames satisfying property B is proved.